Greene and Petty's Criteria: The Quality of Grade II Students' Theme 4 Books - Mandala, Dewa Duta; Sukartono (Universitas Pendidikan Ganesha, 2023)
A good knowledge book is a novel that can accommodate students in solving environmental cases, does not bring wrong thoughts, and can be presented to scientific laws. This book is very useful for teachers as a learning resource to improve student learning outcomes. Through the evaluation of Greene and Petty theory textbooks, this study intends to evaluate the caliber of grade II students' books on subject 4, Clean and Healthy Living, in primary schools. Researchers employed qualitative research methodologies and qualitative research analysis approaches in this study. According to Greene and Petty, the study used ten criteria for high-quality books. The data source used is the book of grade II student themes 4 of the 2013 curriculum. Data were collected during this study using documentation and observation techniques. The strategies used in this work for interactive model data analysis include data reduction, data storage, and data validation. The method used to collect data is sheet analysis, consisting of a set of data collection criteria and tools. Based on the study's results, grade II student books theme 4 of the 2013 curriculum scored 93,5% with high-quality categories.